A theory-based analysis of labour unions in the South African Public Service - Tando Rulashe (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This study provides a theory-based analysis of labour unions in the South African Public Service (SAPS), focusing on the evolving dynamics of labour relations, power structures, and collective bargaining processes. The research investigates how both historical legacies and contemporary socio-economic conditions shape the role of unions within the public sector. Specifically, the study examines the influence of apartheid-era policies, post-apartheid reforms, and the impact of global economic trends on labour organisations. Theoretical frameworks such as institutional theory, social movement theory, and marxist perspectives, along with indigenous frameworks like ubuntu philosophy, worker democracy, liberation unionism, and social movement unionism, underpin the analysis. The research follows a qualitative design, drawing on an in-depth analysis of academic literature, policy documents, legal frameworks, and secondary data sources to uncover trends and patterns in labour relations. Key findings reveal a complex interplay of socio-economic inequalities, political governance, and legislative frameworks that continue to shape union activities within the SAPS. Additionally, the study highlights the importance of socio-cultural dynamics in understanding labour relations within a historically charged environment. This paper contributes to theoretical debates in industrial relations by offering nuanced insights into the challenges and opportunities confronting unions in the South African public sector. The findings have practical implications for policymakers, union leaders, and public administration practitioners aiming to encourage more equitable labour relations and promote social justice. Ultimately, the study provides a framework for rethinking labour union strategies in light of contemporary challenges and the broader pursuit of transformation in the public service.